2020
DOI: 10.1007/s13204-020-01427-6
|View full text |Cite
|
Sign up to set email alerts
|

Jeffery–Hamel flow of hybrid nanofluids in convergent and divergent channels with heat transfer characteristics

Abstract: Described in this article is a numerical study on the Jeffery-Hamel flow of hybrid fluid consisting of Copper and Graphene oxide nanoparticles. The nanofluid are considered as single-phase fluid and their heat transport performance is also investigated. The flow is carried out in a convergent/divergent channel where the channel walls can stretch or shrink. Additionally, the impact of magnetic field on flow and heat transfer analysis are examined. The flow governing equations are modeled under the Boussinesq ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Similarly, Hafeez et al . 37 studied the Jeffery–Hamel flow of copper and Graphite’s oxide/water hybrid nanofluid in the channel using a numerical technique and also talked about the issue of heat transmission. They found that increasing the value of the Reynolds number, it increases the velocity and rate of fluid heat transfer in the convergent channel but not in the divergent channel.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hafeez et al . 37 studied the Jeffery–Hamel flow of copper and Graphite’s oxide/water hybrid nanofluid in the channel using a numerical technique and also talked about the issue of heat transmission. They found that increasing the value of the Reynolds number, it increases the velocity and rate of fluid heat transfer in the convergent channel but not in the divergent channel.…”
Section: Introductionmentioning
confidence: 99%
“…Abumandour et al 5 disclosed the peristalsis driven thermal-viscosity nanomaterial via resilient vertically held pipe. Hafeez et al 6 described the convergent/divergent flow analysis in hybrid nanoliquid under heat transport features. Ramesh et al 7 explored the modified Darcian flow analysis in hybrid nanofluid through convergent-divergent flow channel.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Numerous authors [31][32][33] have researched Jeffery-Hamel flows, which are to obtain an exact similarity solution of the Navier-Stokes equation. Hafeez et al 34 investigated the heat transfer properties of the Jeffery-Hamel flow of hybrid nanofluids in convergent and divergent channels. Kumbinarasaiah and Raghunatha 11 used the wavelet approach to analyze the numerical solution of the Jeffery-Hamel flow.…”
mentioning
confidence: 99%